Highly selective amino-functionalized magnetic molecularly imprinted polymers: absorbents for dispersive solid phase extraction and trace level analysis of chlorophenols in seawater. Issue 84 (26th August 2016) - Shen, Haoyu; Liu, Baiwei; Xiang, Qi; Wang, Chunchun; Mao, Shi Qiang
Abstract : Three-in-one dispersive magnetic solid phase extraction system for preconcentration of trace-level CPs in seawater was established by using as-prepared molecularly imprinted magnetic polymers with effective, fast, and accurate for routine analyses. Abstract : A method of dispersive magnetic solid phase extraction (dMSPE) using magnetic molecularly imprinted polymer ( n Fe3 O4 @NH2 MIP) as an adsorbent coupled with high performance liquid chromatography (HPLC) was developed for the determination of 5 kinds of chlorophenols (CPs) in seawater samples. 8 kinds of n Fe3 O4 @NH2 MIP were synthesized via suspension polymerization by using the 5 different kinds of CPs as templates and 4 different kinds of amines for surface grafting. Compared with seven other kinds of MIP materials and the non-imprinted magnetic polymers ( n Fe3 O4 @NH2 NIPs), the as-prepared n Fe3 O4 @TEPA–PCP-MIP showed excellent extraction performance for CPs with high enrichment efficiencies, short times, high recoveries and reusabilities. Various parameters affecting the extraction efficiency of the dMSPE of the 5 target CPs were optimized, including solution pH, extraction time, desorption time, desorption solution, volume of desorption solution, kinds of absorbents, etc. The results show that under the optimal condition, linearities are obtained ranging from 1 ng L −1 to 5000 ng L −1 with correlation coefficients ( R ) higher than 0.9989 for the target CPs. The recoveries are between 86.5% and 98.8% at the spiked levels with the relative standard deviations (RSDs) in the range of 0.8–8.8%. The limits of detection (LODs) are in the range of 0.18–1.2 ng L −1 and the limits of quantification (LOQs) are between 0.6 ng L −1 and 4.0 ng L −1 . The developed method is successfully applied for real sample analyses, which confirm that it can be applied to routine monitoring for the determination of the CPs in seawater samples.